Human Needs and Conflicts Experienced in The Film Turning Red By Domee Shi3 - Annisa; Rahmat Fajar; Esy Solvera (English Language, Linguistics, Literature, And Education Journal, 2023)
This study analyzes the fulfillment of human needs and the conflicts in fulfilling these needs by the main character in the film Turning Red by Domee Shi. The purpose of this study is to explain how the main character fulfills human needs and to find out the conflicts that occur in fulfilling human needs seen by the main character in the film Turning Red by Domee Shi. Researcher used a psychological approach. Researcher used a qualitative descriptive method. Sources of data in this study are scripts, images and dialogue from the film Turning Red by Domee Shi. In collecting data, researcher used documentation techniques. Then the data were analyzed using descriptive analysis. The results of the analysis in this study indicate that researcher found five levels of human needs using Abraham Maslow's hierarchy of needs theory, namely physiological needs, safety needs, love and belonging needs, self-esteem needs, and self-actualization needs. This study shows that human needs have been fulfilled by the main character in the film Turning Red by Domee Shi. Then, the researcher found three conflicts in fulfilling human needs, especially at the level of self-esteem and self-actualization using Kurt Lewin's conflict theory, namely approach-approach conflict, avoidance-avoidance conflict, and approach-avoidance conflict. This study shows that the main character has resolved conflicts in fulfilling human needs, especially at the level of self-esteem and self-actualization in the film Turning Red by Domee Shi.